History on trial: Evaluating learning outcomes through audit and accreditation in a national standards environment - Brawley, Sean; Clark, Jennifer; Dixon, Chris; Ford, Lisa; Nielsen, Erik; Ross, Shawn; Upton, Stuart (Teaching and Learning Inquiry, 2015)
This paper uses a trial audit of history programs undertaken in 2011-2012 to explore issues surrounding the attainment of Threshold Learning Outcomes (TLOs) in an emerging Australian national standards environment for the discipline of history. The audit sought to ascertain whether an accreditation process managed by the discipline under the auspices of the Australian Historical Association (AHA) could be based on a limited-intervention, “light-touch” approach to assessing attainment of the TLOs. The results of the audit show that successful proof of TLO attainment would only be possible with more active intervention into existing history majors and courses. Assessments across all levels of history teaching would have to be designed, undertaken, and marked using a rubric matched to the TLOs. It proved unrealistic to expect students to demonstrate acquisition of the TLOs from existing teaching and assessment practices. The failure of the “light-touch” audit process indicates that demonstrating student attainment under a national standards regime would require fundamental redevelopment of the curriculum. With standards-based approaches to teaching and learning emerging as international phenomena, this case study resonates beyond Australia and the discipline under investigation.